USAHA PENINGKATAN KOMPETENSI GURU DALAM MENDESAIN MEDIA AUGMENTED REALITY BERBASIS BIM - Wahyu Noviansyah; A.G Tamrin; Taufiq Lilo Adisucipto; Anis Rahmawati (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
The world of education continues to be faced with the challenges of the industrial revolution 4.0 and society 5.0. Advances in technological development, require teachers to be able to develop innovative and creative learning. Digitization of learning is a must in learning activities. Especially the characteristics of the current generation which tends to be digital native. Changes in the educational paradigm are increasingly leading to efforts to integrate Information and Communication Technology (ICT) in learning activities. The Technological Pedagogical Content Knowledge (TPACK) approach is relevant to be applied to learning in the digital era. Therefore, the best way to face these challenges is to increase the TPACK ability of teachers through digital learning media training. One of the digital learning media that is suitable for use in vocational learning is augmented reality. This service is carried out to increase the capacity of Mitra SMK teachers in designing augmented reality-based learning media. The service partners are teachers of SMKN Construction and Property Engineering Expertise (TKP) throughout Greater Solo, including: SMKN 5 and 2 Surakarta, SMKN 2 and 4 Sukoharjo and SMKN 2 Wonogiri. The training method uses face-to-face classical training with demonstration techniques and project-based tutorials. The results of the training show that teachers have a positive perception of training activities. This can be seen from the aspect of teacher satisfaction with the implementation of training, the suitability of the material with the learning needs of SMK, the available facilities and infrastructure and the clarity of the tutor in delivering the material.